Overcoming challenges in using magnesium-based materials for industrial applications using friction-stir engineering. Issue 9 (13th June 2023) - Maqbool, Annayath; Khan, Noor Zaman; Siddiquee, Arshad Noor; Badruddin, Irfan Anjum; Hussien, Mohamed; Khan, Mohammed Imran
Abstract : Using lightweight materials reduces fuel consumption and carbon emissions. Magnesium, a lightweight structural material with interesting properties, performs well during processing and application. Poor ductility of Mg alloys hinders their application in material-forming industries. Grain size reduction significantly improves the ductility in comparison with unprocessed material. Friction stir engineering (FSE) not only provides refinement, homogenisation, and densification of the microstructure, but also helps in eliminating the cast microstructural defects, and fragmentation of the brittle and network-like phases (Mg17 (Al, Zn)12, Al8 Mn5 ) and achieves high-strain rate super plasticity. The current review addresses the challenge of poor ductility and provides insights of the FSE on Mg-based materials to improve ductility by various methods, including the development of metallic foam.